Development of a Solid-Phase Extraction (SPE) Cartridge Based on Chitosan-Metal Oxide Nanoparticles (Ch-MO NPs) for Extraction of Pesticides from Water and Determination by HPLC - Mohamed E. I. Badawy; Mahmoud A. M. El-Nouby; Abd El-Salam M. Marei (International Journal of Analytical Chemistry)
The present study aims to prepare two new types of chitosan-metal oxide nanoparticles (Ch-MO NPs), namely, chitosan-copper oxide nanoparticles (Ch-CuO NPs) and chitosan-zinc oxide nanoparticles (Ch-ZnO NPs), using sol-gel precipitation mechanism, and test them new as adsorbent materials for extraction and clean-up of different pesticides from water. The design of core-shell was implemented by metal oxide core with chitosan as a hard shell after crosslinking mechanism by glutaraldehyde and then epichlorohydrin. The characterizations of the prepared nanoparticles were investigated using Fourier transform infrared spectrometry (FT-IR), zeta potential, scanning electron microscopy (SEM), transmission electron microscope (TEM), and X-ray diffraction (XRD). FT-IR confirmed the interaction between chitosan, metal oxide, and crosslinking mechanism. SEM and TEM explained that the nanoparticles have a spherical morphology and nanosize of 93.74 and 97.95 nm for Ch-CuO NPs and Ch-ZnO NPs, respectively. Factorial experimental design was applied to study the effect of pH, concentration of pesticide, agitation time, and temperature on the efficiency of adsorption of pesticides from water samples. The results indicated that optimum conditions were pH of 7, temperature of 25°C, and agitation time of 25 min. The SPE cartridges were then packed with Ch-MO NPs, and seven pesticides of abamectin, diazinon, fenamiphos, imidacloprid, lambda-cyhalothrin, methomyl, and thiophanate-methyl were extracted from water samples and determined by HPLC. The extraction efficiency of Ch-ZnO NPs was higher than Ch-CuO NPs, but both removed a larger amount of most of tested pesticides than the standard ODS cartridge (C18). The results showed that this method achieves rapid and simple extraction in small quantities of adsorbents (Ch-MO NPs) and solvents. In addition, the method is highly sensitive to pesticides and has a high recovery rate.